Memadukan Rukyatulhilal dengan Perkembangan Sains - Ahmad Junaidi (Jurnal Madania)
Abstract: Integrating Rukyatulhilal with the Development of Science. Hilal (the crescent moon) which is a parameter to determine the begining of the month is a very thin and dim objects. The testimony of sighting it as the basis for the stipulation of the early month of hijri calendar is still frequently subjected to subjectivity. On the other hand, the demand of objectivity as the basic of islamic worshiping is a necessity. The oath enacted against the moon lunar sighting is the only way to assess the objectivity of the witness. Witness in the testimony of sighting the crescent moon must meet some requirements. But what often happens in the field is that there is rarely any assessment of the witness whether it meets the requirements or not. Assessing the honesty and fairness of a witness is not easy. So the development of science and technology is expected to be able to improve the objectivity of sighting the crescent moon, so the results can be accounted for by islamic law and science. Optical and digital imaging technology is one of the bids to increase the objectivity of sighting the crescent moon.